Changing public attitudes toward nuclear energy - Bisconti, Ann Stouffer (Progress in nuclear energy (New series), 2018)
The public has always seen two faces of nuclear energy—the face of immense promise and the face of peril. The more the face of promise presents itself, the more the face of peril fades. Analysis of long-term public opinion trend data and in-depth public opinion research studies shows what influences public opinion about nuclear energy and how public opinion could be influenced in the future. The potential for attitude change is great, as most people take middle positions on nuclear energy and most do not feel very well informed about the subject. Research shows how to bring clarity to the face of promise, which currently is not well defined. In a time of energy abundance, it is necessary to show that nuclear energy is not just another energy option; its unique role as the 24/7 clean air energy source makes nuclear energy vital and irreplaceable. The analysis draws from the 34-year program of public opinion research on nuclear energy sponsored by the Nuclear Energy Institute and directed by Ann Stouffer Bisconti, supplemented by illustrative polling data from the U.S. and other countries.